2018
DOI: 10.1111/aji.13040
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of metallothioneins in myometrium and fetal membranes

Abstract: Temporal-, labor-, and infection-associated increases in MT1 isoforms, MT2A, and MT3 have been observed in fetal membranes and/or myometrium. Furthermore, pro-inflammatory cytokines and bacterial and viral products increased the expression of MT1 isoforms, MT2A, MT3, and MT4 mRNA expression in fetal membranes and myometrium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Thus, the reduced availability of MT1M would be expected to enhance oxidative stress by altered regulation of superoxide radicals, as well as by effects on zinc metabolism [ 37 ]. Additionally, previous research also showed that the expression of MT1M was regulated by pro-inflammatory cytokines, indicating MT1M might participate in the inflammation process as well [ 38 ]. The relationship between MT1M and HCM has not been reported before; therefore, in-depth research is needed to reveal the underlying mechanism of MT1M on HCM.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the reduced availability of MT1M would be expected to enhance oxidative stress by altered regulation of superoxide radicals, as well as by effects on zinc metabolism [ 37 ]. Additionally, previous research also showed that the expression of MT1M was regulated by pro-inflammatory cytokines, indicating MT1M might participate in the inflammation process as well [ 38 ]. The relationship between MT1M and HCM has not been reported before; therefore, in-depth research is needed to reveal the underlying mechanism of MT1M on HCM.…”
Section: Discussionmentioning
confidence: 99%
“…A small study by Lappas et al. demonstrated that MT1‐4 was upregulated in intrauterine tissues in women with PTD complicated by bacterial infection 85 . It has also been shown that MT1A is expressed in the foetal membranes in women delivering preterm 86 and MT1A was higher in membranes close to the rupture site compared with more distant sites in women with spontaneous rupture of the membranes at term 87 .…”
Section: Discussionmentioning
confidence: 99%
“…CHAC2 has a pivotal role in the neutralization of reactive oxygen species, being necessary for the maintenance of human embryonic stem cell self-renewal [ 32 ]. MT1M is critical for regulating oxidative stress, inflammation and hormone signaling in term and preterm labor [ 33 ]. SOSTDC1 , was found expressed in the uterine glandular epithelial cells of the receptive rat endometrium, and thus, may be involved in the onset of endometrial receptivity [ 34 ], while RRM2 expression was downregulated in the RIF endometrium, compared to fertile controls [ 35 ].…”
Section: Discussionmentioning
confidence: 99%